Ophthalmic reasons in unfitness for military service in medical evidence of The Area Military Medical Commission in Lodz - Nowak, Michał S.; Goś, Roman; Śmigielski, Janusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: To assess ocular causes for rejection from the military service. Material and methods: A retrospective review of medical examinations for entry to the military service from The Area Military Medical Commission in Lodz. Ophthalmic examinations were performed according to meet eligibility criteria. We used statistic analysis to review the results. Results: Statistic analysis revealed that during period 1993-2004 ocular diseases were causes of 4.68% rejections from the army. The major ocular causes were high refractive errors. Conclusions: 1. Ocular diseases are important causes for rejection from the army (4.68% in total). 2. Major ocular causes for rejection are: high refractive errors, glaucoma and chronic diseases of the choroid, retina and optic nerve.